To Determine Mean Change In Weight Of Patients Undergoing Maxillomandibular Fixation - Mushtaq, Osama; Shuja, Eruj; Ahmed, Momina; Hassan, Amna; Asim, Muhammad Adil; Siddiq, Maimona (Journal of Rawalpindi Medical College, 2023)
Objective: Optimum management of patient needs is the most important step for the restoration of form and function. Maxillomandibular fixation is one of the treatment modalities used very frequently in maxillofacial surgery. This study aims to determine the mean change in weight in patients undergoing Maxillomandibular Fixation. Methods: This observational cross-sectional study was conducted at the Department of Oral and Maxillofacial Surgery Foundation University Medical College from 27th April 2018 to 22nd January 2019. This study included patients male and female, who presented with maxillofacial trauma, orthognathic surgery and procedures in which MMF ( Maxillomandibular fixation ) was indicated were included in this study. Pre-operative weight was measured in kilograms with an analogue weight machine and designated as W1. Patients were advised to a liquid diet and kept on follow-up. After four weeks of MMF again weight of the patient was measured and designated as W2. Follow-up was done through the patient’s contact number. Results: In this study, the mean weight of patients preoperatively was 59.46±12.23 Kg. The postoperative mean weight of patients was 57.81±11.58 Kg. A decrease of 1.65 Kg was seen in the patient’s weight postoperatively. No significant difference was seen for weight change in patients postoperatively with age, gender, educational status, occupational status, socioeconomic status and an indication of MMF. Conclusion: Results of this study showed weight loss in patients who underwent maxillomandibular fixation. This factor should be considered during the perioperative period to prevent postoperative complications, postoperative weight loss, and malnutrition of patients undergoing maxillomandibular surgery and reflect the need for guidance on diet postoperatively, mainly directed to frequency of feeding and high protein liquid diet and nutritional supplements. Keywords: Body mass index, Facial trauma, Maxillomandibular Fixation, Mandibular fracture, Open reduction internal fixation, Orthognathic surgery, Weight loss.